An Analysis of the Influence of Multilayer Films with Low Thermal Conductivity on the Inner Surfaces of CCPP Headers and Steam Pipelines on Their Thermal Stress State - Yury. A. Radin; Tatiana. S. Kontorovich (Current Perspectives on Chemical Sciences Vol. 8, 2021)
One of the main critical elements affecting the resource of combined cycle power plants (CCPP) heat recovery steam generators (HRSG) is the outlet high-pressure superheater header. The protection of headers, heat-exchange pipes, steam pipelines from corrosion is carried out by maintaining the correct water-chemical regime, which causes the formation of thin protective films. The combination of a protective film layer and a layer, for example, of heating steam condensate on the inner surface of pipelines with a heat carrier flowing inside, creates a significant thermal resistance of the multilayer wall and helps to reduce thermal stresses arising in them under variable conditions. These protective films, which protect pipes from corrosion, are formed on the inner surfaces of CCPP heat recovery steam generators pipe systems at temperatures above 230°C and good deaeration. The paper presents the results of computational analysis of the effect of thin multilayer protective films on the CCPP HRSG headers and steam pipelines thermal stress state under various variable operating conditions, in particular, during start-ups from various thermal states and thermal shocks. Calculations were carried out at different film thicknesses and under the condition that their thermal conductivity is lower than the thermal conductivity of base metal. As a result of the calculations, it was possible to determine the heating modes of headers and steam pipelines, for which the protective films influence is the greatest. It is shown that multilayer protective films noticeably affect the stresses arising in the pipe and the accumulation of damage, mainly at large temperature disturbances (during thermal shocks). The effect of protective films on the non-heated pipes thermal stressed state was evaluated in terms of reducing resource consumption and accumulating equivalent operating hours under variable modes. It is shown that the resource of a high-pressure superheater outlet header 426 x 34 mm can be increased by 6 % only due to the presence of a protective film 50 microns thick with a thermal conductivity equal to half the thermal conductivity of the base metal.